Microplastics in Agricultural Soils - Navya, K.; Kiran, K. Sai; Kumar, E. Ajay (Chronicle of Bioresource Management, 2024)
Microplastics have been a major source of pollution, a problem for the environment worldwide They can endanger human health and food security once they get into agricultural soils. Large quantities of plastic fragments are left behind after crop cultivation. The leftover plastic waste eventually breaks down into microscopic pieces, that will have a diameter of less than 5mm. Numerous alterations in the physico-chemical properties of the soil, such as porosity, enzymatic and microbiological activity, plant growth, and yield, are caused by microplastics. By altering their properties, microplastics can modify a number of important soil biogeochemical processes, which can have a variety of implications on the functions and activities of soil microorganisms.